Probiotic Potential of Indigenous (Bacillus sp. RCS1, Pantoea agglomerans RCS2, and Bacillus cereus strain RCS3) Isolated From Cobia Fish (Rachycentron canadum) and Their Antagonistic Effects on the Growth of Pathogenic Vibrio alginolyticus, Vibrio harveyi, Streptococcus iniae, and Streptococcus agalactiae - Amenyogbe, Eric; Huang, Jian-sheng; Chen, Gang; Wang, Wei-zheng (Frontiers in Marine Science, 2021)
Fish farming is facing challenges due to the frequent incidences of infectious diseases, high risk of disease infection of cobia fish and insufficient knowledge of their gut microbiota. Large scale fish farming faces many environment stresses, which effects their immune systems, growth performance and physiological homeostasis, resulting in their increasing susceptible to infections. Antibiotics have been used previously, and have effectively decreased the incidence of disease infection but its excessive use has resulted in bacterial resistance. Some of the most common bacterial infections of cobia fish include streptococcosis, vibriosis, furunculosis and mycobacteriosis, and Photobacterium sp, are considered as emerging fish diseases in aquaculture. Probiotics could be useful in reducing or limiting the incidence of severe disease infections or outbreaks. Therefore, the present study aimed to isolate the indigenous bacteria Bacillus spp. RCS1 (MW560712), Pantoea agglomerans strain RCS2 (MW560713), and Bacillus cereus RCS3 (MW560714) from the gut of juvenile’s cobia, having advantageous assets or positive characteristics. The antagonistic effects of isolated bacterial strain on the growth of pathogens, including Vibrio alginolyticus, Vibrio haeveyi, Streptococcus iniae, and Streptococcus agalactiae were investigated, which showed inhibitory effects against all these pathogens. Generally, the characteristics displayed by these probiotics indicated that they could be used as probiotics in aquaculture industry.